2018
DOI: 10.1116/1.5022283
|View full text |Cite
|
Sign up to set email alerts
|

Direct metal etch of ruthenium for advanced interconnect

Abstract: In this work, Ru wires patterning by direct etch are evaluated for a potential 5 nm technology node. The characteristics of Ru etching by varying the bias voltage, total flow rate and Cl2/(O2+Cl2) gas flow ratio are studied in an inductively couple plasma etching chamber. Ru sidewalls profile with a tapering angle of 90° and Ru to SiO2 hard mask etch selectivity of 6 are achieved. The authors show the feasibility of patterning lines with an aspect ratio up to 3.5 and lines with a critical dimension down to 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…[26][27] However, the majority of deposits achieved via FEBID of organometallic precursors require concurrent or post-deposition purification steps. One particularly interesting class of precursors are Ru-based organometallic compounds, which gain more and more importance regarding the manufacturing of electronic chips, 28 building of interconnect wires, 29 and most importantly for the repair of EUVL masks. [30][31][32] There are a few studies addressing Ru-based FEBID processes, which report rather low metal contents of the corresponding deposits in the absence of purification steps.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27] However, the majority of deposits achieved via FEBID of organometallic precursors require concurrent or post-deposition purification steps. One particularly interesting class of precursors are Ru-based organometallic compounds, which gain more and more importance regarding the manufacturing of electronic chips, 28 building of interconnect wires, 29 and most importantly for the repair of EUVL masks. [30][31][32] There are a few studies addressing Ru-based FEBID processes, which report rather low metal contents of the corresponding deposits in the absence of purification steps.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the damascene implementation of ruthenium lines is hampered by the availability of optimized CMP. A semi-damascene integration approach is a proposed solution for multilevel Ru interconnect [ 266 , 267 ]. Danny Wan et al reported that Ru films were patterned using EUV single exposure and a subtractive etching step to generate lines with CD down to 10.5 nm.…”
Section: Metal Materials Interconnectmentioning
confidence: 99%
“…With the successful suppression of the grain-boundary scattering effect, a reduction in total wire resistivity of more than 30% was achieved. The result suggests by that enlarging the grain sizes of Ru and combining it with a subtractive patterning process [ 266 , 267 ], the physical limitation of nano-grain structures in damascene Ru can be solved.…”
Section: Metal Materials Interconnectmentioning
confidence: 99%
“…Ruthenium (Ru) is already used in semiconductor fabs as a barrier metal for interconnects. , Ru is listed in international roadmap for devices and systems (IRDS) as the next for future-generation metal interconnects in logic devices and as a metal electrode for DRAM capacitors. Thus, there is a semiconductor ecosystem already in place for ruthenium thin-film deposition, patterning and etch of sub-20nm Ru features with high yield and low defectivity. Our research in ruthenium-based MacEtch aims to leverage this existing Ru ecosystem in the semiconductor industry.…”
Section: Introductionmentioning
confidence: 99%